Modern brand management: innovation - Banks, Jonathan (Henry Stewart Talks, 2010)
Problems exacerbated by the Credit Crunch, Value destruction, Commoditization of Fast Moving Consumer Goods categories, Growth of private label, Increased promotional reliance, Rise of the discounters, How to add value and protect brands from price based competition